Análise dos padrões ventilatórios em ratos pós-acidente vascular encefálico isquêmico - Eduardo Henrique Ferreira (2022)
The stroke is considered the main cause of disability in the Brazilian adult population, causing great functional losses in its carriers, which are motor, cognitive and sensory. Much is known about these changes mentioned above, however, research should be carried out to understand the impact of stroke on ventilation. For this reason, we evaluated the impact of stroke on neural control of breathing in rats through whole-body plethysmography, using the stimuli of hypercapnia (7% CO2, 21% O2, balanced with nitrogen (N2)) and hypoxia (10% O2 and N2 90%). Our data suggest that bilateral common carotid occlusion surgery (BCAo), considered as a model of global ischemia, caused an attenuation of the animals' ventilatory response to hypercapnia and hypoxia stimuli, and in hypercapnia the ischemia animals showed significant differences in the respiratory rate (RR), ventilation (VE) and O2 consumption (VO2). In the hypoxia stimulus, they showed significant differences in RR and VE. We also performed the quantification of apneas, however there was no significant difference in the ischemia group. To evaluate possible functional, motor, and behavioural changes, we performed the neurological score, grip test and the object recognition task, respectively. The ischemia group showed no significant differences in these parameters, indicating that the ischemia model used may have been mild/moderate for these animals. Finally, cell death labeling was performed with Fluoro-Jade in the brainstem and striatum. We saw that this model of ischemia did not cause cell death in the areas responsible for central chemoreception, and the areas investigated were: the Nucleus of the Solitary Tract (NTS), Raphe Obscurus (RO), Raphe Magnus (RM) and rostral ventrolateral region of the medulla, however, the ischemic insult may have caused damage to the circuitry of these neurons, since the data obtained showed changes in some respiratory variables, such as respiratory rate (RR) and ventilation (VE). More studies should be carried out to clarify the reason why these changes occurred, in order to contribute to a better understanding of the impact of a central lesion on the neural control of ventilation.